INTERNATIONAL LAW AND POLITICS: AN ANALYSIS OF MARTTI KOSKENNIEMI’S ARTICLE - Zeynep Erhan Bulut (Karatekin Hukuk Dergisi)
This paper critically reviews The Politics of International Law by Martti Koskenniemi, a seminal work that examines the liberal concept of the Rule of Law through a critical lens. Koskenniemi highlights the inherent tensions between normativity and concreteness in international law, as well as the interplay between rule-based and policy-based approaches. While his analysis offers significant insights into the political nature of international law and its dependence on state sovereignty, his arguments are marked by ambiguity and a lack of definitive conclusions. This paper summarises Koskenniemi’s key arguments, including his critique of liberalism, the indeterminacy of international legal argumentation, and the role of international lawyers in navigating the relationship between law and politics. The discussion evaluates these ideas from multiple perspectives, incorporating views from critical legal theory and legal realism. Although Koskenniemi raises important questions about sovereignty, sources of law, and the objectivity of international legal norms, his work is critiqued for its circular reasoning and lack of clarity. This review concludes that Koskenniemi’s contribution lies in his nuanced critique of the liberal foundations of international law, even as his failure to resolve key dilemmas leaves room for further scholarly debate. The aim of this paper is to review The Politics of International Law by outlining a straightforward framework, without engaging in a deep academic discussion.